Sporoderm-Removed Spore Powder May Suppress the Proliferation, Migration, and Invasion of Esophageal Squamous Cell Carcinoma Cells Through PI3K/AKT/mTOR and Erk Pathway - Jingyan Liu Master degree; Tao Zeng Doctor degree (Integrative Cancer Therapies)
Tumor metastasis is a key factor of therapeutic failure in tumor patients, but the underlying molecular mechanism remains to be explored and novel effective curative strategies are urgently required. Emerging evidence suggests that sporoderm-removed Ganoderma lucidum spore powder can suppress tumor growth and metastasis. However, the molecular mechanisms of action remain elusive. In the present study, we investigated the effects and mechanisms of sporoderm-removed Ganoderma lucidum spore powder against esophageal squamous cell carcinomas (ESCC). The expression of MCP-1 in esophageal squamous cell carcinoma cells was detected by Western blotting. The MTS assay was used to assess the esophageal squamous cell carcinoma cells viability. The clone formation assay was used to evaluate to the proliferation ability of KYSE140 and KYSE510 cells. Apoptosis and the cell cycle were analyzed by flow cytometry. Wound healing and Transwell assays were used to analyze the migration of KYSE140 and KYSE510 cells. Invasion was also analyzed by the Transwell assay. The expressions of PI3K, AKT/p-AKT, Erk/p-Erk, JNK1, and mTOR were detected by Western blotting. We found that the MCP-1 protein was highly expressed in KYSE140 and KYSE510. In addition, sporoderm-removed Ganoderma lucidum spore powder treatment was found to inhibit esophageal squamous cell carcinoma cell proliferation, to block the cell cycle, to induce cell apoptosis and to inhibit cell migration and invasion. Finally, we found that sporoderm-removed Ganoderma lucidum spore powder decreased the expression of PI3K/AKT/mTOR and Erk signaling pathways. Taken together, these findings demonstrate that sporoderm-removed Ganoderma lucidum spore powder suppresses esophageal squamous cell carcinomas by involving MCP-1, regulated by PI3K/AKT/mTOR and Erk signal pathways.